Capital Structure and Firms’ performance: Evidence form UK Listed Firms - Jin, Han (2010)
This study is to investigate the effect which capital structure has had on firms’ performance using a panel data sample representing of 346 UK listed firms during 2004-2007. The result showed that a firm’s capital structure had a significant negative impact on the firm’s performance measure of return on assets. This study also found that the short-term debt to total assets (STDTA) and long-term debt to total assets (LTDTA) have a negative effect on the firm’s return on assets as well. Moreover, a firm’s size and firm’s growth opportunity has been found to have a significant and positive effect on a firm’s return on assets, whereas the risk has been found to have negative relationship with the firm’s return on assets.